UJI AKTIVITAS EKSTRAK ETANOL BUAH PARE (Momordica charantia L.) TERHADAP PENURUNAN KADAR GLUKOSA DARAH PADA MENCIT PUTIH JANTAN - Aditya Maulana Perdana Putra; Ratih Pratiwi Sari (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2018)
Degenerative disease is a disease that causes damage or destruction of tissues or organs of the body due to unhealthy lifestyle where one of them is diabetes mellitus disease. The increasing number of sufferers from year to year and expensive treatment encourages some people to seek alternative medicine. which is widely used as a traditional medicine is pare (Momordica Charantia). Pare contains a lot of secondary metabolites that allegedly can lower blood glucose levels with various mechanisms of action. This is the basis of this research. The purpose of this study was to find out whether the pare extract can lower blood glucose levels of mice and get the optimal dose of pare ethanol extract that can be used to lower blood glucose levels of mice. The sample of the research was the extract of pare (Momordica charantia L.) in Bati-bati sub-district which was ± 3 months old. The test animals used in this study were 25 white male mice aged 3 months with an average weight of 20-40 g. The method used was oral glucose tolerance test with five treatment groups: positive control (metformin 90mg / kgBW), ethanol extract group of 50mg / kgBW, 75mg / kgBB and 100mg / kgBW and negative control group (aquadest 0,5ml / 20grBW). The results showed that pare contains alkaloids and steroids. Provision of ethanol extract of pine fruit at doses of 75 mg / kgBW can decrease the blood glucose level of white mice (Mus musculus) significantly P <0.05. Thus, the extract of ethanol pare fruit can be used as a decrease in blood reduction effect of white male mice glucose level glucose levels.